(untitled) (Journal of Shaheed Suhrawardy Medical College, 2012)
Automated sensor based blood culture system is superior to traditional two steps or biphasic methods regarding time of isolation and avoiding contamination. The present study documented various aspects of blood culture isolates done in a well set automated system (BacT/ALERT 3D, BIOMERIUX, USA) at Dhaka city. As per monthly distribution of samples, number of samples showed increased trend from March and declining trend in November with peak in July, August, September and October. Average detection time was found as 20 hours. Among the bacterial pathogens isolated, Salmonella typhi was the most common (66.62%) followed by Salmonella paratyphi (S. paratyphi A & B 22.21%). Antibiotic susceptibility patterns (%) of the isolated organisms are shown in Table - VI. The results are not much divergent in respect of particular pathogens. The mostly focused results of common blood culture pathogen Salmonella typhi and Salmonella paratyphi show sensitivity pattern of over 95% towards Amoxyclav (98.0% & 99.36%), Aztreonam, Amikacin, Cefaclor, Cefixim, Cettazidime, Ceftriaxone, Cephalexine and Ciprofloxacin. Almost all the strains were found resistant towards Azithromycin. No satisfactory sensitivity was obtained towards Cotrimoxazole, Gentamicin, Mecillinam and Nalidixic acid. Gram negative bacteria including Escherichia coli as blood culture isolates were resistant towards used panel of antibiotics except Ciprofloxacin, Cotrimoxazole, Gentamicin and Mecillinam. Over 90% strains showed resistant towards Amoxycillin and Azithromycin. The study established that blood culture reports with positive growth and antimicrobial susceptibility can be generated within maximum of 72 hours by automated culture system. DOI: http://dx.doi.org/10.3329/jssmc.v1i2.12162 Journal of Shaheed Suhrawardy Medical College Vol.1, No.2, December 2009 p.21-26